A Caribbean Visionary and His Literary Collection, Karlene Saundria Nelson. Issue 1 (April 2021) - Nelson, Karlene Saundria
The voices of West Indian writers in the 1950s changed the landscape for Literature emerging out of the West Indies. These powerful literary voices were a means of creating and recording a facet of West Indian history and cultural heritage. West Indian writers wrote their stories through their own eyes. John Hearne was one of the most eloquent voices among them. He became a known voice in the West Indian literary world, using his recognition to facilitate the indigenous West Indian Literature genre's development. He was also a prominent Jamaican political and social commentator. The John Hearne archive not only produced an important historical picture of the development of the West Indian Literature genre, but West Indian political history, and changes in the cultural and social fabric of the West Indian society, with special emphasis on Jamaica. This paper aims to present this archive as a fundamental body of primary resources for historical research.